CONSCIOUS ADOLESCENCE: PREVENTION AND SUPPORT FOR TEENAGE PREGNANCY AT HUMBERTO DE CAMPOS MUNICIPAL SCHOOL - Almeida da Silva, Flaelma; de Lima, Diana; Alves Quaresma, Márcia; Felipe da Silva Marçal, Luis; Lima Sol Suignard, Jaisa; Bolsanelo Menezes Vieira, Lara; Fernanda Paiva Amorim, Maria; Claudia Andrade, Ana (Health and Society, 2024)
The field research focused on teenage pregnancy had the general objective of sensitizing and educating the school community about the challenges associated with early pregnancy, promoting prevention, quality of life formation, and appropriate support. To achieve these objectives, the research utilized an exploratory and descriptive methodology, employing both qualitative and quantitative approaches to gain a comprehensive understanding of the topic. During the research, questionnaires and interviews were conducted to collect data on students’ knowledge about contraceptive methods, the consequences of teenage pregnancy, and the importance of family planning. Additionally, discussion groups were held to promote open dialogue about sexuality, prevention, and support for pregnant teenagers. The findings indicated significant gaps in understanding of contraceptive methods, family planning, and the implications of teenage pregnancy among the participants. Consequently, most participants expressed a need for more information and educational resources on the subject. The educational and awareness activities were well-received, and participants reported an improved understanding of the issues addressed. The research also highlighted the importance of adequate support for pregnant teenagers, emphasizing the need for emotional and social support in schools. Thus, the field research not only contributed to raising awareness about teenage pregnancy but also provided practical directions for future interventions, focusing on preventive education and support for pregnant teenagers within the school environment.